Communication and Democracy in the Twenty-First Century: The challenge of formation - Urribarri, Raisa (2015)
This paper presents an overview about the changes in the relation between communication, technology and politics in the twenty-first century. It proposes a reflection on the challenges introduced by the advent of a medium such as the Internet, which allows interaction and the visibility of counter-hegemonic movements, practices and discourses. Based on a hermeneutic reading, away from the bipolar simplification and founded on gadamerianas notions of horizon, formation and dialogue, highlights the centrality of listening as a basis for the construction of genuinely democratic societies.